Pneumococcal Vaccination Provides Substantial Value for Money for Canadians. (4th October 2017) - Peloquin, Francois; Breton, Marie-Claude; Wasserman, Matt; Wilson, Michele; McDade, Cheryl; Farkouh, Raymond
Abstract: Background: Introduction of pneumococcal conjugate vaccines (PCV) to the Canadian childhood routine immunization schedules (RIS) resulted in significant benefits. The 7-valent PCV was added to all provinces' RIS between 2002 and 2006. The 10-valent PCV was used in Ontario and Quebec for 12 to 18 months in 2009 and 2010. The 13-valent PCV was marketed in 2010 and rapidly adopted by all provinces. Direct vaccine protection reduced incidence of invasive pneumococcal disease (IPD), pneumonia (PNE) and acute otitis media (AOM) in vaccinated children. Indirect vaccine protection also reduced the burden of disease (BOD) in other age groups. Sensible public funds allocation motivates continued evaluation of public health programs. Objective: To evaluate the economic impact of PCVs to Canadian society following nationwide RIS implementation. Methods: Canadian databases and literature were reviewed to obtain pre- and post-PCV incidence of IPD, PNE and AOM, as well as direct and indirect medical costs (reported in 2017 CAD). Case counting index date was set to Jan 2005, at which point PCV RIS were implemented for over 90% of Canadians. A steady state scenario using pre-PCV incidence rates was projected to Dec 2015 to estimate the number of cases without PCVs. Averted cases were obtained by subtracting the cases reported from the estimated case count without PCVs. Disease specific costs were assigned to averted cases and vaccine spend was subtracted from the total to obtain net savings to Canadian society. Results: Successive implementation of PCVs on the provinces' RIS saved 2, 365 lives and resulted in net savings of CAD 203 million between Jan 2005 and Dec 2015. These savings stem from averted direct and indirect medical costs associated with IPD, PNE and AOM cases. Conclusion: Introduction of PCVs resulted in reduced pneumococcal burden of disease and net economic benefits to Canadian society. Disclosures: F. Peloquin, Pfizer: Employee, Salary; M. C. Breton, Pfizer: Employee, Salary; M. Wasserman, Pfizer: Employee, Salary; M. Wilson, Pfizer: Consultant, Consulting fee; C. McDade, Pfizer: Consultant, Consulting fee; R. Farkouh, Pfizer: Employee, Salary